Sistem Pengambilan Keputusan Pemilihan Menu Terlaris Menggunakan Metode SMART (Simple Multi Attribute Rating Technique) - Yazid Azriel; Galuh Saputri (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract In this decision-making system study, SMART (Simple Multi Attribute Rating Technique) is used to select the best-selling menu from all the recommended menus. This multi-criteria decision-making technique is based on the theory that each other method consists of several criteria using a value, and each criterion has a weight that describes its importance compared to other criteria. The SMART method is used to calculate the evaluation criteria, because the SMART approach can work in complex situations and allows analysis with minimal data. . So we need a decision support system that uses the Simple Multi Attribute Rating Technique method to make recommendations for the best menu candidates based on taste test criteria, display tests, presentation tests, and time tests. The end result of this SPK is that we can provide the best recommendations for job seekers according to the specified criteria. Keywords: Decision support system, Simple Multi Attribute Rating Technique